Effects of Hunting on a Puma Population in Colorado. Issue 1 (8th March 2021) - Logan, Kenneth A.; Runge, Jonathan P.
ABSTRACT: We investigated effects of regulated hunting on a puma ( Puma concolor ) population on the Uncompahgre Plateau (UPSA) in southwestern Colorado, USA. We examined the hypothesis that an annual harvest rate averaging 15% of the estimated number of independent individuals using the study area would result in a stable or increasing abundance of independent pumas. We predicted hunting mortality would be compensated by 1) a reduction in other causes of mortality, thus overall survival would stay the same or increase; 2) increased reproduction rates; or 3) increased recruitment of young animals. The study occurred over 10 years (2004–2014) and was designed with a reference period (years 1–5; i.e., RY1–RY5) without puma hunting and a treatment period (years 6–10; i.e., TY1–TY5) with hunting. We captured and marked pumas on the UPSA and monitored them year‐round to examine their demographics, reproduction, and movements. We estimated abundance of independent animals using the UPSA each winter during the Colorado hunting season from reference year 2 (RY2) to treatment year 5 (TY5) using the Lincoln‐Petersen method. In addition, we surveyed hunters to investigate how their behavior influenced harvest and the population. We captured and marked 110 and 116 unique pumas in the reference and treatment periods, respectively, during 440 total capture events. Those animals produced known‐fate data for 75 adults, 75 subadults, and 118 cubs, which we used to estimate sex‐ and life stage‐specific survival rates. In the reference period, independent pumas more than doubled in abundance and exhibited high survival. Natural mortality was the major cause of death to independent individuals, followed by other human causes (e.g., vehicle strikes, depredation control). In the treatment period, hunters killed 35 independent pumas and captured and released 30 others on the UPSA. Abundance of independent pumas using the UPSA declined 35% after 4 years of hunting with harvest rates averaging 15% annually. Harvest rates at the population scale, including marked independent pumas with home ranges exclusively on the UPSA, overlapping the UPSA, and on adjacent management units were higher, averaging 22% annually in the same 4 years leading to the population decline. Adult females comprised 21% of the total harvest. The top‐ranked model explaining variation in adult survival ( S ̂ ) indicated a period effect interacting with sex. Annual adult male survival was higher in the reference period ( S ̂  = 0.96, 95% CI = 0.75–0.99) than in the treatment period ( S ̂  = 0.40, 95% CI = 0.22–0.57). Annual adult female survival was 0.86 (95% CI = 0.72–0.94) in the reference period and 0.74 (95% CI = 0.63–0.82) in the treatment period. The top subadult model showed that female subadult survival was constant across the reference and treatment periods ( S ̂  = 0.68, 95% CI = 0.43–0.84), whereas survival of subadult males exhibited the same trend as that of adult males: higher in the reference period ( S ̂  = 0.92, 95% CI = 0.57–0.99) and lower in the treatment period ( S ̂  = 0.43, 95% CI = 0.25–0.60). Cub survival was best explained by fates of mothers when cubs were dependent ( S ̂ mother alive  = 0.51, 95% CI = 0.35–0.66; S ̂ mother died  = 0.14, 95% CI = 0.03–0.34). The age distribution for independent pumas skewed younger in the treatment period. Adult males were most affected by harvest; their abundance declined by 59% after 3 hunting seasons and we did not detect any males >6 years old after 2 hunting seasons. Pumas born on the UPSA that survived to subadult stage exhibited both philopatry and dispersal. Local recruitment and immigration contributed to positive growth in the reference period, but recruitment did not compensate for the losses of adult males and partially compensated for losses of adult females in the treatment period. Average birth intervals were similar in the reference and treatment periods (reference period = 18.3 months, 95% CI = 15.5–21.1; treatment period = 19.4 months, 95% CI = 16.2–22.6), but litter sizes (reference period = 2.8, 95% CI = 2.4–3.1; treatment period = 2.4, 95% CI = 2.0–2.8) and parturition rates (reference period = 0.63, 95% CI = 0.49–0.75; treatment period = 0.48, 95% CI = 0.37–0.59) declined slightly in the treatment period. Successful hunters used dogs, selected primarily males, and harvested pumas in 1–2 days (median). We found that an annual harvest rate at the population scale averaging 22% of the independent pumas over 4 years and with >20% adult females in the total harvest greatly reduced abundance. At this scale, annual mortality rates of independent animals from hunting averaged 6.3 times greater than from all other human causes and 4.6 times greater than from all natural causes during the population decline. Hunting deaths were largely additive and reproduction and recruitment did not compensate for this mortality source. Hunters generally selected male pumas, resulting in a decline in their survival and abundance, and the age structure of the population. We recommend that regulated hunting in a source‐sink structure be used to conserve puma populations, provide sustainable hunting opportunities, and address puma‐human conflicts. © 2021 The Wildlife Society. RESUMEN: Investigamos los efectos de la cacería regulada en la población de pumas ( Puma concolor ) de la Uncompahgre Plateau (UPSA) en el suroeste de Colorado, USA. Exploramos la hipótesis de que una cosecha anual con una tasa promedio del 15% del número estimado de pumas independientes que están usando el área de estudio resultaría en una abundancia estable o un incremento de pumas independientes. Nuestra predicción de que la mortalidad por cacería seria compensada por: 1) una reducción en otras causas de mortalidad, por lo tanto, la supervivencia se mantendría igual o incrementaría; 2) un incremento en la tasa reproductiva; o 3) un incremento en el reclutamiento de pumas jóvenes. Este estudio se llevó a cabo a lo largo de 10 años (2004–2014) y fue diseñado con un periodo de referencia (años 1 al 5; RY1–RY5) sin cacería de pumas y un periodo de tratamiento (años 6–10; i.e., TY1–TY5) con cacería de pumas. Capturamos y marcamos pumas en la UPSA y se llevó a cabo el monitoreo a lo largo de todo el año para examinar la demografía, reproducción y movimientos de los pumas. Estimamos la abundancia de pumas independientes que usaban la UPSA cada invierno durante la estación de cacería de pumas en Colorado usando el año 2 (RY2) como referencia al año de tratamiento 5 (TY5) usando el método de Lincoln‐Petersen. Adicionalmente, llevamos a cabo prospecciones con cazadores para investigar como el comportamiento de los cazadores influía la cosecha y la población de pumas. Capturamos y marcamos un total de 110 y 116 pumas únicos dentro del periodos de referencia y de tratamiento, respectivamente, a lo largo de un total de 440 eventos de captura. Esos pumas produjeron datos de mortalidad con información conocida para 75 adultos, 75 sub‐adultos y 118 cachorros, con los cuales se estimaron tasas de supervivencia específicas por sexo y etapas de vida. En el periodo de referencia la abundancia de pumas independientes se incrementó a más del doble y exhibieron una supervivencia alta. La mortalidad natural fue la mayor causa de muerte en pumas independientes, seguida de causas producidas por seres humanos (e.g. atropellamientos, control de depredadores). En el periodo de tratamiento, los cazadores mataron 35 pumas independientes, adicionalmente capturaron y dejaron en libertad a 30 pumas en la UPSA. La abundancia de pumas independientes se redujo en un 35% después de 4 años de cacería con tasas de aprovechamiento con un promedio anual de 15% en la UPSA. Las tasas de aprovechamiento a la escala de población incluyendo pumas independientes marcados con ámbitos hogareños exclusivos dentro de la UPSA, con sobreposición en la UPSA y en unidades adyacentes de manejo fueron mayores, en promedio 22% anualmente durante los mismos 4 años que llevaron a la población al declive. Las hembras adultas comprendieron 21% de la cosecha total. El mejor modelo que explicaba la variación en la supervivencia ( S ̂ ) de los adultos indicaba un efecto del periodo interactuando con el sexo. La supervivencia anual de los machos fue más alta durante el periodo de referencia ( S ̂  = 0.96, 95% CI = 0.75–0.99) que durante el periodo de tratamiento ( S ̂  = 0.40, 95% CI = 0.22–0.57). La supervivencia anual de las hembras fue 0.86 (95% CI = 0.72–0.94) en el periodo de referencia y 0.74 (95% CI = 0.63–0.82) durante el tratamiento. El mejor modelo de supervivencia en hembras sub‐adultas, mostro que la supervivencia fue constante a través de los periodos de referencia y tratamiento ( S ̂  = 0.68, 95% CI = 0.43–0.84), donde la supervivencia de los machos sub‐adultos exhibió el mismo patrón de supervivencia de los machos adultos: más alta en el periodo de referencia ( S ̂  = 0.92, 95% CI = 0.57–0.99) y menor en el periodo de tratamiento ( S ̂  = 0.43, 95% CI = 0.25–0.60). La supervivencia de los cachorros se explica mejor por el destino de sus madres, cuando estos son dependientes ( S ̂ madres vivas  = 0.51, 95% CI = 0.35–0.66; S ̂ madres muertas  = 0.14, 95% CI = 0.03–0.34). La distribución por edades de los pumas independientes estuvo sesgada a animales jóvenes durante el periodo de tratamiento. Los machos adultos fueron los más afectados por el aprovechamiento, su abundancia se redujo en un 59% después de 3 temporadas de cacería, y una ausencia de machos >6 años de edad después de 2 temporadas de cacería. Los pumas nacidos en la UPSA que sobrevivieron a la etapa sub‐adulta exhibieron características filopátricas y de dispersión. El reclutamiento local y la inmigración contribuyeron al crecimiento positivo en el periodo de referencia. Sin embargo, el reclutamiento no compenso por la pérdida de machos adultos y parcialmente compenso por la pérdida de hembras durante el periodo de tratamiento. El intervalo promedio entre nacimientos fue similar entre los periodos de referencia y tratamiento (periodo de referencia = 18.3 meses, 95% CI = 15.5–21.1; periodo de tratamiento = 19.4 meses, 95% CI = 16.2–22.6), mientras que el tamaño de camada (periodos de referencia = 2.8, 95% CI = 2.4–3.1; periodo de tratamiento = 2.4, 95% CI = 2.0–2.8) y las tasas de parición (periodo de referencia = 0.63, 95% CI = 0.49–0.75; periodo de tratamiento = 0.48, 95% CI = 0.37–0.59) declinaron ligeramente durante el periodo de tratamiento. Cazadores exitosos de pumas usaron perros, seleccionaron fundamentalmente machos y cosecharon pumas en 1−2 días (mediana). Encontramos a la escala de población una tasa de aprovechamiento anual de 22% del número de pumas independientes en un periodo de 4 años y donde >20% de hembras adultas en la cosecha total redujeron en cantidad la abundancia de pumas. A esta escala, las tasas anuales de mortalidad de los pumas independientes por caceria fueron en promedio 6.3 veces mayores que todas las otras causas producidas por seres humanos, y 4.6 veces mayores que todas las causas de mortalidad natural durante la reducción en la población. La mortalidad por cacería era aditiva y la reproducción y el reclutamiento no compensaron a la mortalidad por cacería. Encontramos que los cazadores de pumas seleccionaron pumas machos, resultando en una reducción de la supervivencia, abundancia de machos y la estructura de edades dentro de la población. Recomendamos que la cacería regulada con base en una estructura poblacional de fuente‐sumidero puede ser utilizada para conservar a las poblaciones de pumas, proporcionando oportunidades para la cacería sustentable de pumas y redirigir el conflicto entre pumas y seres humanos. RÉSUMÉ: Nous avons examiné les effets d'une chasse régulée sur une population de puma ( Puma concolor ) dans le plateau de l'Uncompahgre (UPSA) dans le sud‐ouest du Colorado. Nous avons examiné l'hypothèse qu'un taux annuel de récolte de 15% du nombre estimé de pumas indépendants utilisant l'aire d'étude maintiendrait l'abondance ou accroîtrait l'abondance de pumas. Nous avons prédit que la mortalité par la chasse serait compensée par: 1) une réduction des autres causes de mortalité, entrainant une augmentation ou stabilisation de la survie; 2) une augmentation du taux de reproduction; ou 3) une augmentation du recrutement de jeunes individus. L'étude a été conduit durant, et a été construite autour d'une période de référence (années 1 à 5) sans chasse aux pumas et une période de traitement (années 6 à 10) avec une chasse aux pumas. Nous avons capturé et marqué des pumas dans l'aire d'étude (UPSA) et les avons suivis toute l'année pour récolter des données concernant leur démographie, reproduction et mouvement. L'abondance de pumas indépendants a été estimée dans l'USPA à chaque hiver durant la saison de chasse aux pumas au Colorado de l'année de référence 2 (RY2) à l'année de traitement 5 (TY5) en utilisant la méthode de Lincoln‐Petersen. De plus, nous avons sondé les chasseurs afin d'apprendre comment leur comportement influençait la récolte et la population de puma. Durant les périodes de référence et traitement, 110 et 116 pumas ont respectivement été capturés et marqués, durant 440 évènements de capture. Ces pumas ont produit des données dont le sort est connu pour 75 adultes, 75 subadultes, et 118 juvéniles qui ont été utilisés afin de modéliser le taux de survie de chaque sexe et groupe d'âge. Durant la période de référence, l'abondance des pumas indépendants a plus que doublé en abondance et montré un haut taux de survie. La mortalité naturelle était la cause principale de décès, suivie par les mortalités reliées à l'humain. Durant la période de traitement, les chasseurs ont tué 35 pumas indépendants et capturé puis relâché 30 pumas. L'abondance de pumas indépendants a décliné de 35% après 4 années de chasse avec des taux de récolte moyennant 15% dans l'UPSA. Les taux de récoltes à l'échelle de la population incluant des individus dont le domaine vital était à l'intérieur de l'USPA, chevauchant l'USPA, ou en périphérie de l'USPA étaient plus élevés et approchaient 22% durant les quatre années précédant le déclin de la population. Les femelles adultes représentaient 21% de la récolte total. Le meilleur modèle expliquant la variation dans la survie ( S ̂ ) des adultes incluait un effet de la période en interaction avec le sexe. Le taux de survie des mâles adultes était plus élevé durant la période de référence ( S ̂  = 0.96, 95% CI = 0.75–0.99) que durant la période de traitement ( S ̂  = 0.40, 95% CI = 0.22–0.57). Le taux de survie des femelles adultes était de 0.86 (95% CI = 0.72–0.94) durant la période de référence et de 0.74 (95% CI = 0.63–0.82) durant la période de traitement. Le meilleur modèle du taux de survie des femelles subadultes a démontré que la survie était constante entre les deux périodes de traitement ( S ̂  = 0.68, 95% CI = 0.43–0.84) alors que le taux de survie des mâles subadultes a montré la même tendance que les mâles adultes: plus élevé durant la période de référence ( S ̂  = 0.92, 95% CI = 0.57–0.99) que durant la période de traitement ( S ̂  = 0.43, 95% CI = 0.25–0.60). Le taux de survie des petits était le mieux expliqué par le sort de la mère alors que les petits étaient dépendants ( S ̂ mère en vie  = 0.51, 95% CI = 0.35–0.66; S ̂ mère en vie  = 0.14, 95% CI = 0.03–0.34). La structure des âges des pumas indépendants a décliné durant la période de traitement. Les mâles adultes étaient les plus affectés par la récolte, leur abondance a décliné de 59% après trois saisons de chasse et aucun individu de plus de 6 ans n'était présent après deux saisons de chasse. Les pumas nés dans l'UPSA qui ont survécu au stage subadulte ont exhibé de la philopatrie et de la dispersion. Le recrutement local et l'immigration ont contribué au taux de croissance durant la période de référence. Le recrutement n'a pas compensé pour la perte de mâles adultes et a compensé partiellement pour la perte de femelles adultes durant la période de traitement. L'intervalle moyen des naissances est demeuré similaire (période de référence = 18.3 mo., 95% CI = 15.5–21.1; période de traitement = 19.4 mo., 95% CI = 16.2–22.6), alors que la taille des portées (période de référence = 2.8, 95% CI = 2.4–3.1; période de traitement = 2.4, 95% CI = 2.0–2.8) et le taux de parturition (période de référence = 0.63, 95% CI = 0.49–0.75; période de traitement = 0.48, 95% CI = 0.37–0.59) ont diminué légèrement durant la période de traitement. Les chasseurs de pumas qui ont eu du succès ont utilisé des chiens, ils sélectionnaient primairement les mâles et ont récolté des pumas à l'intérieur de 1–2 jours (médiane). Nous avons trouvé qu'un taux de récolte moyen avoisinant 22% du nombre estimé de pumas indépendants sur quatre ans et avec >20% de femelles adultes dans la récolte réduisait grandement l'abondance de puma. À cette échelle, le taux de mortalité annuel provenant de la chasse était en moyenne 6.3 fois plus grand que le taux provenant de tous les autres causes de mortalité humaine et 4.6 fois plus grand que le taux de mortalité de source naturelle durant la période de déclin de la population. La mortalité par la chasse était largement additive et la reproduction et le recrutement n'ont pas compensé pour cette source de mortalité. Nous avons trouvé que les chasseurs montraient une sélection pour les pumas mâles, entrainant alors une réduction de la survie et de l'abondance des mâles et impactant la structure des âges de la population. Nous recommandons qu'une chasse régulée dans une structure source‐puit peut être utilisée afin d'aider la conservation des pumas, procurer des opportunités de chasse durable, et adresser les conflits pumas‐humains.